Frame Repertoires at the Genre Level: An Automated Content Analysis of Character, Emotional, and Moral Framing in Satirical and Regular News. Issue 1 (1st January 2023) - Brugman, Britta C.; Burgers, Christian; Beukeboom, Camiel J.; Konijn, Elly A.
ABSTRACT: Previous research suggests that, compared to regular news, satirical news has its own frame repertoire, which differs by outlet characteristics (e.g. medium type, political leaning). We analyzed two large corpora of satirical and regular news: television show episodes (8, 925, 180 words) and online written articles (64, 301, 669 words) of liberal and conservative outlets for character, emotional, and moral framing. Contrary to expectations, findings revealed consistent framing differences between the satirical and regular news genres, which were not moderated by medium type or political leaning. Thereby, this study shows how genre-level frame repertoires can offer deeper insights into cross-genre differences in news coverage.